2015
DOI: 10.1111/afe.12113
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term influence of partial cutting on hemlock looper (Lepidoptera:Geometridae) parasitism

Abstract: 1 Silvicultural treatments are suggested as an option for controlling insect defoliators, although the effects of treatment on parasitism remain widely unknown. Therefore, in the present study, the influence of partial cutting on hemlock looper Lambdina fiscellaria (Guenée) (Lepidoptera: Geometridae) parasitism is studied by comparing two cutting intensities (25% and 40% reduction of stand basal area) against controls. 2 Laboratory reared hemlock looper pupae are periodically exposed in each plot to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Also, thinning helps to improve tree resistance to defoliation (Fuentealba and Bauce 2012;Seehausen et al 2015). For instance, light thinning (25% of total basal area removed) of balsam fir and white spruce led to higher tolerance to budworm defoliation through increased foliage production, particularly on hydric and subhydric sites (Fuentealba and Bauce 2012), with similar findings reported for hemlock looper dynamics (Seehausen et al 2015). Aerial spraying of insecticide during spruce budworm outbreak has been shown to reduce host tree mortality by as much as 44% (Fuentealba et al 2022).…”
Section: Stand-replacing Disturbance Vs Gap Dynamicsmentioning
confidence: 71%
See 1 more Smart Citation
“…Also, thinning helps to improve tree resistance to defoliation (Fuentealba and Bauce 2012;Seehausen et al 2015). For instance, light thinning (25% of total basal area removed) of balsam fir and white spruce led to higher tolerance to budworm defoliation through increased foliage production, particularly on hydric and subhydric sites (Fuentealba and Bauce 2012), with similar findings reported for hemlock looper dynamics (Seehausen et al 2015). Aerial spraying of insecticide during spruce budworm outbreak has been shown to reduce host tree mortality by as much as 44% (Fuentealba et al 2022).…”
Section: Stand-replacing Disturbance Vs Gap Dynamicsmentioning
confidence: 71%
“…Because smaller retention patches (0.2 ha) more effectively support the regeneration of shade-tolerant species, a combination of dispersed retention and aggregate retention could be used to produce desired combinations of early and late successional species on the landscape (Franklin et al 2018). Also, thinning helps to improve tree resistance to defoliation (Fuentealba and Bauce 2012;Seehausen et al 2015). For instance, light thinning (25% of total basal area removed) of balsam fir and white spruce led to higher tolerance to budworm defoliation through increased foliage production, particularly on hydric and subhydric sites (Fuentealba and Bauce 2012), with similar findings reported for hemlock looper dynamics (Seehausen et al 2015).…”
Section: Stand-replacing Disturbance Vs Gap Dynamicsmentioning
confidence: 99%
“…Parasitoids' sensitivity to temperature and humidity (Hance et al 2007) could be a key issue affecting their occurrence. Seehausen et al (2015) observed that heavy thinning operations significantly reduced larval parasitism of the hemlock looper (Lambdina fiscellaria (Guenée)).…”
Section: The Relationships Between Stand Characteristics and Natural mentioning
confidence: 99%
“…Stand characteristics can have direct or indirect effects on pest insect populations. Stand characteristics, such as basal area, tree age, number of trees per hectare, or fragmentation, may affect parasitism or predation by providing a variety of habitats and microclimatic conditions (Roland 1993;Seehausen et al 2015). Sawfly parasitism has been observed to be more effective in pure pine forests than in mixed-species forests (Herz and Heitland 2003).…”
Section: Introductionmentioning
confidence: 99%